2009
DOI: 10.1093/schbul/sbp143
|View full text |Cite
|
Sign up to set email alerts
|

IQ Trajectory, Cognitive Reserve, and Clinical Outcome Following a First Episode of Psychosis: A 3-Year Longitudinal Study

Abstract: Comparison of current and estimated premorbid IQ in schizophrenia suggests that there are subgroups with low IQ, deteriorated IQ (DIQ), or preserved IQ and that this is established by psychosis onset. There are no controlled studies examining the trajectory of these IQ subgroups longitudinally or their relationship with clinical and social outcomes. Of 129 individuals with first-episode schizophrenia or schizoaffective disorder, 25% showed stable low IQ, 31% showed stable IQ in the average/high range, and 44% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
102
4
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(121 citation statements)
references
References 70 publications
(87 reference statements)
12
102
4
3
Order By: Relevance
“…Amminger et al (2002) further suggested that untreated psychoses compromise some aspects of cognitive functions. Later Joyce et al (2005) revealed that half of people with schizophrenia in this study had preserved IQ in normal range after the onset of disorder but there was evidence of a specific impairment in special working memory even in those with high/average IQ; (40%) had generalized cognitive decline, similar results were also revealed by Lesson, et al (2009).…”
Section: Introductionsupporting
confidence: 83%
See 1 more Smart Citation
“…Amminger et al (2002) further suggested that untreated psychoses compromise some aspects of cognitive functions. Later Joyce et al (2005) revealed that half of people with schizophrenia in this study had preserved IQ in normal range after the onset of disorder but there was evidence of a specific impairment in special working memory even in those with high/average IQ; (40%) had generalized cognitive decline, similar results were also revealed by Lesson, et al (2009).…”
Section: Introductionsupporting
confidence: 83%
“…It has been observed during our clinical experience that clients with depression and anxiety disorders often have reality contact and their social, occupation and daily functioning is much better then people with schizophrenia because it is more severely disturbed mental disorder. Lesson, et al (2009) also showed that IQ at psychosis onset rather than premorbit IQ predicts a more severe illness.…”
Section: Introductionmentioning
confidence: 96%
“…In light of the heterogeneity in intellectual performance patterns observed in schizophrenia and given the inconsistencies in the literature regarding issues of intellectual decline, premorbid impairments, and preserved abilities, a typology comprising preserved, deteriorated, and premorbidly impaired intellectual ability patterns has been proposed and received partial support (Badcock, Dragović, Waters, & Jablensky, 2005;Leeson et al, 2011).…”
Section: Patterns Of Intellectual Ability In Schizophreniamentioning
confidence: 99%
“…We calculated a difference score (IQ minus premorbid IQ) in order to see whether the estimated deterioration was associated with cannabis use (see also Leeson et al, 2011), and found this to be the case. This raises the possibility of a neuroprotective action of cannabis.…”
Section: Difference Between Iq and Premorbid Iq In Relation To Cannabmentioning
confidence: 99%